The shock recovery experiments of CI chondrites - Nakahashi, Toru; Miyahara, Masaaki; Yamaguchi, Akira; Kobayashi, Takamichi; Yusa, Hitoshi; Tomioka, Naotaka (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OA] Antarctic Meteorite, Tue. 14 Nov. / Entrance Hall (1st floor), National Institute of Polar Research conference object